Tinjauan Pengaturan Mengenai Pemenuhan Hak Anak Sebagai Korban Kejahatan Asusila di Indonesia - Rinanti, Pitra; Sigiro, Talenta Ribka; Alifiandra, Muhammad Reiza; Fadhillah, Muhammad Arif; Prasetyo, Handoyo (Media Hukum Indonesia (MHI), 2024)
When discussing sexual crimes against children, it is not only about the concept of sexual offenses but also about the nature of perpetrators and victims and how society and law enforcement handle such crimes. Data shows that cases of sexual crimes against children are increasing, indicating that children still frequently fall victim to sexual crimes. This proves that it is difficult for children to feel safe and unaffected by sexual crimes. In this study, the author uses a normative juridical research method that is qualitative in nature, which relies on a legal norm existing in legislation, accompanied by norms that have developed in society. This research is descriptive-analytical, meaning the author elucidates the legislation related to various legal theories that are the object of research. The Criminal Code (KUHP) has regulated sexual offenses in Chapter XIV, which covers 20 criminal law provisions divided into the material of indecency in public, such as acts of openly violating decency, dissemination of indecent material, facilitating access to indecent material, and adultery. The Criminal Code also regulates acts of molestation, rape, indecent acts related to abortion or pregnancy prevention, and acts of indecency. Comprehensive regulations regarding the rights of children as victims of sexual offenses in Indonesia have also been stipulated in Law Number 23 of 2002 Concerning Child Protection and related articles in the Criminal Code.